PENINGKATAN HASIL PRODUKSI PADA PRODUSEN BENIH PADI - Fahri Ali Ahzar; Yulfan Arif Nurohman (ABDI MAKARTI, 2022)
Central Java is included in the top three in national scale rice production. The agricultural sector, especially rice production, is still the mainstay for farmers in Indonesia. The increase in national rice production must be accompanied by an increase in the production of quality rice seeds. In Solo Raya, there is an Association of Seed Producers and Traders or Ikatan Produsen dan Pedagang Benih (IPPB) which consistently produces rice seeds to meet the needs of local and national markets. Community service activities with partners from the Association of Seed Producers and Traders are carried out to increase the production of quality rice seeds according to market needs.